DC Super Hero Girls : finals crisis : an original graphic novel - Fontana, Shea (DC Comics, 2016)
"Super Hero Girls features DC Comics' most powerful and diverse line-up of female characters as relatable teens, playing out across multiple entertainment content platforms and product categories to create an immersive world. Icons including Wonder Woman, Supergirl, Batgirl, Harley Quinn, Bumble Bee, Poison Ivy, Katana and many more make their unprecedented teenaged introduction, as each character has her own storyline that explores what teen life is like as a Super Hero"--